Aproximaciones a la definición jurídica. - Barahona Novoa, Alberto (2012)
This article takes under consideration the principal distinctiveness of the definitions used to define legal concepts according to the law, written form a theoretical and lexicographic viewpoint. From a sample driven from the Costa Rican law, the main definitions used in the forensic written language are to be exposed. From this analysis, the nuisances that a congressman might find are also revealed. The law implied definitions are a fundamental piece for the right understanding of the spirit of all set of laws that are in command of the social behavior. On behalf of the above, the intention of a true evaluation form the actual lexicographic point of view is an assignment that begins with this piece of writing.